Cameroon : Selected Issues. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper aims at providing an empirical underpinning to fiscal policy reforms implemented by the authorities by estimating the size of fiscal multipliers in Cameroon, using a novel long quarterly data set and looking separately at the impact of changes in revenue, and government consumption and investment. The impact of government spending and taxes depends on country characteristics and the stage of the business cycle. The analysis shows that revenue and capital expenditure multipliers in Cameroon are small and comparable to those of other sub-Saharan African and low-income countries. The revenue multiplier is close to nil which implies that revenue-based fiscal consolidation would be less harmful to growth in the medium term. Compared to its peers in sub-Saharan Africa, Cameroon's revenue multiplier is smaller as is its tax burden relative to the regional average. Conversely, government expenditure can more significantly affect output in the medium term, although the consumption multiplier is unexpectedly much higher than the investment one.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet